Exploring The Responses of Students Generation Z Toward Disciplined English Teacher in English Language Teaching (ELT) - Prastya , Rio Laksamana; Marlia, Rika; Indra Setiawan, Guntur Tri ((JELE) Journal Of English Language and Education, 2024)
Teaching by emphasizing the disciplines to the students sometimes was judged as old school method especially for generation Z students. The aim of this research was to investigate the perceptions and responses of the students generation Z toward disciplined English teacher in English language teaching the material. This research used mix method where the participants were 168 students from semi-military campus. To acquire the distribution of students’ response toward disciplined English teacher in teaching English language, this research used questionnaire. Furthermore, to collect the data deeper, this research applied in-depth interviews. The finding showed that the students indicated positive attitudes even if they enrolled strict class. It occurred because the English teacher could act as fair-minded regulator and tutor inside the class. Therefore, even if applying strict English class was assumed as traditional method in teaching, apparently it could offer positive aspects toward the students. Basically, in this context, the teacher in order to conduct English language teaching always prioritized student-centered learning. However, even if English language teaching by using disciplined method still demonstrated positive trend, but this research believed that the strongest aspect influencing this finding because of the students’ education background. Thus, this research affirmed that conducting disciplined teaching method in English language teaching (ELT), it could offer drawback or advantage, it depends two factors: How the teacher delivered the material, and the students’ background.